Operation Sherdil : Battle of Bajaur - Abid Mumtaz (Rawalpindi Inter Service Public Relations (ISPR) and Hilal Publications, 2019)
The Battle of Bajaur or Operation Sherdil was a military offensive in the Bajaur region of Pakistan launched by the Frontier Corps and supported by a Combat Brigade of the Pakistan Army.
Include Color Illustrations, Maps and Bibliography
A Memoir by Major General Abid Mumtaz
Keywords: military offensive -- Operation